2007
DOI: 10.1007/s00432-007-0258-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of cytokeratin positive cells in bone marrow of gastric cancer patients

Abstract: Bone marrow (BM) is a prognostically relevant indicator organ of micrometastasis; however, the clinical importance of BM micrometastasis in gastric cancer patients is not yet known. In the present study, the BM of 267 consecutive patients with primary gastric cancer was examined for tumor cells using immunocytochemical techniques. Real-time quantitative RT-PCR was used to ensure that the tumor cells were detected properly. Among the 267 cases analyzed, 30 cases (11.2%) had cytokeratin-positive cells in the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Nevertheless, authors proposed to continue these studies, in particular in multicenter protocol investigations. At the same time some observations have been published where the clinical relevance of DTCs in gastric cancer patients was not observed [1921]. Recently published review of Bidard et al [22] allows to conclude that problem of DTCs in gastric cancer is relevant for clinics but it is not fully solved and needs to be clarified to improve the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, authors proposed to continue these studies, in particular in multicenter protocol investigations. At the same time some observations have been published where the clinical relevance of DTCs in gastric cancer patients was not observed [1921]. Recently published review of Bidard et al [22] allows to conclude that problem of DTCs in gastric cancer is relevant for clinics but it is not fully solved and needs to be clarified to improve the treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, evidence has been accumulating that the presence of DTCs in bone marrow (BM) is a prognostic indicator for patients with various types of cancer. However, recent studies indicate that all the patients with DTCs do not necessarily develop recurrence and/or metastasis (6,7). In a recent study we demonstrated that DTCs are observed in BM even in patients with early-stage gastric cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow DTCs have been reported by several detection techniques in surgically resected gastric cancers: CK18 [33]; CK2-immunostaining [34]; anti-human epithelial antigen (Ber-EP4) [35]; CK20 RT-PCR [36], CK20/CK19/CEA RT-PCR [37], CK7/CK8 RT-PCR [38], CEA/CK20/TFF1/MUC2 RT-PCR [39]. About half of these studies reported a significant negative prognostic impact on metastases-free and/or overall survival.…”
Section: Dtcsmentioning
confidence: 99%